Trichocline maxima (Compositae, Mutisieae) a rare Pampean daisy rediscovered after 70 years in Uruguay - Pasini, Eduardo; Bonifacino, José Maurício; Piccin Torchelsen, Fábio (Iheringia, Série Botânica., 2021)
Trichocline maxima was considered probably extinct but has been rediscovered in northern Uruguay after almost 70 years since its last record in this country. We provide an updated description of the species, an indication of a lectotype and we discuss morphology, axonomy, nomenclature, geographical distribution, and conservation status of the species. An identification key for the species of the genus in Uruguay and Brazil is also presented.